O Almirante Tamandaré na Campanha Oriental - Armando de Senna Bittencourt (Navigator)
The subject of this essay is the Brazilian political-military involvement, during the years 1864-1865, intervening in the Oriental Republic of Uruguay civil war between the Blanco and Colorado Parties supporters. Its object is the analyses of the Vice-Admiral Baron of Tamandaré’s and the Brazilian diplomats’ actions during the conflict. This Brazilian military intervention in Uruguay was interpreted as an aggression to his country’s interests by Francisco Solano López, the Paraguayan dictator, and is the starting point of the Tríplice Aliança War against Paraguay (1865-1870), the second bloodiest conflict in the Americas’ History.